PENGELOLAAN POJOK BACA DALAM MENUNJANG BUDAYA LITERASI ANAK USIA DINI - Iffah Mukhlisah; Amin, Laila Hidayatul; Trisnawati, Septian Nur Ika; Fitriyah Al Hidayah; Munailah Nida Fauizah (Kreasi: Jurnal Pengabdian Masyarakat, 2025)
Literacy activities, especially reading, are still not yet part of the culture in the Pakel Village community, Andong District, Boyolali Regency. It is necessary to build productive and effective habits to improve this starting from childhood. The school environment at the elementary education level, namely Raudhatul Atfhal and Kindergarten, is one way to cultivate literacy through the reading corner program. Through community service activities, it is hoped that schools will be able to increase literacy rates from an early age in a fun way. In addition, schools are able to manage Human Resources, Infrastructure, the environment and funding to manage the reading corner optimally and professionally. Management of the reading corner is a short activity through training, programmed and sustainable by means of mentoring the management of the reading corner by Field Lecturers and students. The main findings of this program include three aspects of social transformation. First, from an institutional perspective, the Village Literacy Committee was formed as a new institution that manages the sustainability of the program. Second, from a behavioral perspective, there was an increase in the frequency of children's reading and changes in parenting patterns in accompanying literacy activities. Third, from a leadership perspective, five local champions emerged from among teachers and housewives.